MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMP NEGERI 1 TUNGKAL ULU PADA MATERI BIOTEKNOLOGI MELALUI MODEL PROJECT BASED LEARNING - Sofyana, Nana; Yelianti, Upik (Inspiratif Pendidikan, 2023)
His Classroom Action Research aims to improve students’ critical thinking skills at SMP Negeri 1 Tungkal Ulu in Biotechnology material through a Project Based Learning model. This research was conducted at SMPN 1 Tungkal Ulu. The subjects of this study were students of class IX A with a total of 30 students. This research was conducted in January 2022 - February 2022 even semester of the 2020/2021 school year. This classroom action research was carried out using the research cycle model from Kemmis and Mc. Taggart. This research was conducted through four stages, namely action planning, action implementation, observation/evaluation and reflection as a basis for re-planning for further research. In cycle I, students’ critical thinking skills in Biotechnology material in cycle I obtained a percentage of 56.6% with a total of 17 students who received a completeness score of ≥65. In the second cycle of research, a percentage of 86.67% was obtained with a total of 26 students who received a completeness score of ≥65. The percentage of action monitoring instruments in cycle I obtained a percentage of 65% and increased in cycle II by obtaining a percentage of 87%. Then the same thing happened to the results of monitoring student actions in cycle I which obtained a percentage of 64% and experienced an increase by obtaining a percentage of 84%. The implication of this classroom action research is that the critical thinking skills of class IX A students in Biotechnology material can be increased by applying the Problem Based Learning approach in their learning process.